Progress toward third-order parametric down-conversion in optical fibers - Cavanna, Andrea; Hammer, Jonas; Okoth, Cameron; Ortiz-Ricardo, Erasto; Cruz-Ramirez, Hector; Garay-Palmett, Karina; U'Ren, Alfred B.; Frosz, Michael H.; Jiang, Xin; Joly, Nicolas; Chekhova, Maria (Physical Review A, 2020)
Optical fibers have been considered an optimal platform for third-order parametric down-conversion since they can potentially overcome the weak third-order nonlinearity by their long interaction length. Here we present, in the first part, a theoretical derivation for the conversion rate both in the case of spontaneous generation and in the presence of a seed beam. Then we review three types of optical fibers and we examine their properties in terms of conversion efficiency and practical feasibility.
CRIS-Team WoS Importer:2020-04-10